Influence of Different Exercise Types on Health-Related Quality-of-Life in Men With Depressive Disorder in South Korea - Kyungjin Kim; Kyo-Man Koo (Frontiers Media S.A., 2022)
The aim of the study was to determine the influence of different exercise types on health-related quality of life (QOL) in men with depressive disorder (DD) in South (S) Korea. The data of 385 men aged 19 with DD were collected in S. Korea. The Euro Quality of Life 5 Dimensions (EQ-5D) index and Korea National Health and Nutrition Examination Survey (KNHANES) questionnaires were used to establish the purpose of this study. Furthermore, the complex sampling model was applied to investigate the influence of different exercise types on health-related QOL in participants. When reviewing the outcomes, the strength exercise and walking had significant influences on health-related QOL in men with DD in S. Korea. However, the flexibility exercise did not have a significant influence on them. Based on the results, strength exercise and walking were effective exercise types to increase levels of health-related QOL in men with DD in S. Korea.